Unpacking wonder: from curiosity to comprehension. Issue 1 (9th June 2020) - Paulson, Steve; Shiota, Michelle "Lani"; Henderson, Caspar; Filippenko, Alexei V.
Abstract: From the macrocosm of the universe to the microcosm of the human body, our discoveries about ourselves and the natural world continue to spark our experience of awe and wonder . But how exactly does science define and explain the experience of awe and wonder? Social psychologist Michelle Shiota, writer Caspar Henderson, and astrophysicist Alex Filippenko unpack the emerging science behind the emotions of awe and wonder, including their role in our ongoing quest for understanding and knowledge.